Growth, Inequality and Well-Being: Comparisons across Space and Time - Carola Grün; Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2003)
We use several well-being measures that combine average income with a measure of inequality to undertake international, intertemporal, and global comparisons of well-being. The conclusions emerging from the analysis are that our well-being measures drastically change our impression of levels of well-being of countries. They also significantly affect the ranking of countries, when compared to rankings based on real per capita incomes. These results appear not very sensitive to the data on inequality which this analysis is based upon. However, since the inclusion of inequality has an important impact on well-being comparisons, it is of great importance to generate more consistent and intertemporally as well as internationally comparable data on inequality that are necessary for such comparisons.
Keywords: I31; D63; 330; Lebensstandard; Einkommensverteilung; Sozialprodukt; Sozialer Indikator; Vergleich; Welt